2017
DOI: 10.1016/j.jpeds.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Early Caffeine Prophylaxis and Risk of Failure of Initial Continuous Positive Airway Pressure in Very Low Birth Weight Infants

Abstract: Objective To test the hypothesis that early caffeine treatment on the day of birth, compared with later treatment in very low birth weight (VLBW, <1500 g) infants receiving continuous positive airway pressure (CPAP) therapy, is associated with a decreased risk of CPAP failure in the first week of life. Study design Multicenter, observational cohort study in 366 US neonatal intensive care units. We evaluated inborn, VLBW infants discharged from 2000 to 2014, who received only CPAP therapy without surfactant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
18
2
1
Order By: Relevance
“…In recent years, it has been suggested that premature infants can be benefited from earlier using of caffeine, which was associated with improved hemodynamics (28) and reduced incidence and severity of acute kidney injury (29,30). Early caffeine using was associated with improved blood pressure and systemic blood flow, and heart rate, left ventricular output, and stroke volume were not significantly affected.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been suggested that premature infants can be benefited from earlier using of caffeine, which was associated with improved hemodynamics (28) and reduced incidence and severity of acute kidney injury (29,30). Early caffeine using was associated with improved blood pressure and systemic blood flow, and heart rate, left ventricular output, and stroke volume were not significantly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results on early caffeine administration A retrospective analysis conducted by PATEL et al [73] on VLBW infants (birthweight <1500 g) receiving initial CPAP (on day of life 0) compared the effect of early caffeine (day of life 0) versus routine caffeine (day of life 1-6). The results demonstrated no difference in CPAP failure defined as invasive mechanical ventilation or surfactant therapy on day of life 1-6 (22% versus 21%, adjusted odds ratio (aOR) 1.05), in exposure to a maximal inspiratory oxygen fraction >0.3 in the first week of life (27% versus 32%, aOR 1.05) and in the total duration of CPAP therapy (median 3 versus 2 days, aOR 1.02).…”
Section: Bpd and Long-term Pulmonary Outcomesmentioning
confidence: 99%
“…Starting caffeine in the first day of life increased from 21% in 2000 to 67% in 2014. 4 It has been suggested that all extremely preterm infants should receive caffeine in the very first minute of life to minimise the risk of intubation, in association with surfactant administration during non-invasive respiratory support. 5 But is earlier caffeine treatment better in very preterm infants?…”
Section: Is Earlier Better When It Comes Giving Caffeine To Preterm Imentioning
confidence: 99%